The Element Of Bad Faith In The Cancellation Of The Mark "Pentakosta"(Study of Decision Number 1/Pdt.Sus.HKI/Merek/2021/ PN.Niaga.JktPst) - Fitri Arianti (Ipso Jure, 2024)
The application for trademark registration must be made by the applicant in good faith, which is regulated in Law Number 20 Year 2016 on Trademarks and Geographical Indications. This thesis research aims to find out and analyze the Court Decision related to the cancellation of the "PENTAKOSTA" trademark which has an element of bad faith and how the basis of the judge's consideration in deciding the case of cancellation of the "PENTAKOSTA" trademark. The type of research used in this study is normative legal research. By using the approach of legislation and case approach. From the results of this study it can be concluded that the relationship between the cancellation of registered trademarks with good faith is on the application for registration of the trademark and the Panel of Judges who decided to cancel the trademark after reviewing the bad faith. In the study of Decision Number 1/Pdt.Sus.HKI/ Merek/2021/PN.Niaga.JktPst is not appropriate in applying the law of evidence which is that there is no finding of bad faith in the registration of the trademark by the Defendant. In addition, the legal consequences of the cancellation of the trademark "PENTAKOSTA" is the end of legal protection provided by the state.